Researching and Acting: Exploring and Improving the Provision of Academic Support for Newly Appointed Staff in a Higher Education Institution in Ireland - Roisin Donnelly (Networks: An Online Journal for Teacher Research, 2003)
My current professional role is as an academic working in a learning and teaching centre supporting other academics in a higher education institution in Ireland. In my attempts to become a more developed self-reflective practitioner, there are times when it helps me to take a time-out from my daily teaching practice and instead put some time and energy into clarifying for myself the kinds of values and commitments I hold as a professional in my practice. Earlier this academic year, I undertook a piece of action research as one such time-out. This paper reports how I decided to take a close, critical look at my own practice and to develop and refine insights as to the nature of that practice. This project is part of an ongoing process that I will continue to explore for as long as I work in academic support in higher education.